2014
DOI: 10.1210/en.2013-2032
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Antitumor Drug OSI-906, a Dual Inhibitor of IGF-1 Receptor and Insulin Receptor, on the Glycemic Control, β-Cell Functions, and β-Cell Proliferation in Male Mice

Abstract: The IGF-1 receptor has become a therapeutic target for the treatment of cancer. The efficacy of OSI-906 (linstinib), a dual inhibitor of IGF-1 receptor and insulin receptor, for solid cancers has been examined in clinical trials. The effects of OSI-906, however, on the blood glucose levels and pancreatic β-cell functions have not yet been reported. We investigated the impact of OSI-906 on glycemic control, insulin secretion, β-cell mass, and β-cell proliferation in male mice. Oral administration of OSI-906 wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…We previously reported that the once daily administration of 40 mg/kg of OSI-906 for 7 days significantly increased β cell proliferation and β cell mass 25 . Similarly, OSI-906 had significantly increased the β cell mass and β cell proliferation by day 7 in the present study (Fig.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…We previously reported that the once daily administration of 40 mg/kg of OSI-906 for 7 days significantly increased β cell proliferation and β cell mass 25 . Similarly, OSI-906 had significantly increased the β cell mass and β cell proliferation by day 7 in the present study (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…We previously showed that the administration of OSI-906 at 50 or 75 mg/kg not only induced hyperglycemia and hyperinsulinemia but also reduced the survival rate of mice 25 . In contrast, OSI-906 at 40 mg/kg once daily for 7 days elicited sustained hyperglycemia, but not a low survival rate 25 . In this study, we used 45 mg/kg of OSI-906 for 7 days, and no adverse effects on the survival rate were seen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5b). A number of studies using pharmacological [23, 24] or genetic [2527] tools have demonstrated that insulin resistance leads to beta cell hyperplasia in rodents, and the protease inhibitor serpin B1 was recently identified as a liver-derived circulating factor mediating this response in insulin-resistant mice [5]. In the context of nutrient-induced insulin resistance, however, the respective contributions of nutrients themselves vs their indirect effect through insulin resistance on beta cell proliferation remain unclear, and in this regard our study provides important insights.…”
Section: Discussionmentioning
confidence: 99%
“…However, besides to the involvement of GSK3 in tumor development, it is also a key enzyme in glycogen synthesis and the overall IGF-1 R/IR signaling is crucial for regulating glucose metabolism23. Due to the findings that OSI-906 decreased acute glucose consumption dose-dependently in starved NCI-H292 cells42 and that C57BL/6 J mice showed a deteriorated glucose tolerance64 we examined markers of energy metabolism in the BALB-CTA, too. Although we were able to detect a slightly elevated phosphorylation of the energy sensor AMPK after OSI-906 treatment, we found no difference in ATP content or oxygen consumption on day 22 of the BALB-CTA.…”
Section: Discussionmentioning
confidence: 99%